2019
DOI: 10.3390/nano9050733
|View full text |Cite
|
Sign up to set email alerts
|

As(III) Removal from Aqueous Solution by Calcium Titanate Nanoparticles Prepared by the Sol Gel Method

Abstract: Arsenic (As) contamination of water is a serious problem in developing countries. In water streams, arsenic can be as As(V) and As(III), the latter being the most toxic species. In this work, an innovative adsorbent based on CaTiO3 nanoparticles (CTO) was prepared by the sol-gel technique for the removal of As(III) from aqueous solution. X-ray diffraction of the CTO nanoparticles powders confirmed the CTO phase. Transmission electron microscopy observations indicated an average particle size of 27 nm, while en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
2
2
0
Order By: Relevance
“…Thus, XPS results revealed that As(III) is adsorbed onto PP@TiO 2 and is partially oxidized to As(V). Similar behavior was reported by Tamayo et al [19] for As(III) removal from aqueous solution on calcium titanate nanoparticles. The partial oxidation of As(III) to As(V) could be due to the presence of physio-sorbed oxygen and surface hydroxyl groups.…”
Section: X-ray Photoelectron Spectroscopy (Xps) Studiessupporting
confidence: 89%
“…Thus, XPS results revealed that As(III) is adsorbed onto PP@TiO 2 and is partially oxidized to As(V). Similar behavior was reported by Tamayo et al [19] for As(III) removal from aqueous solution on calcium titanate nanoparticles. The partial oxidation of As(III) to As(V) could be due to the presence of physio-sorbed oxygen and surface hydroxyl groups.…”
Section: X-ray Photoelectron Spectroscopy (Xps) Studiessupporting
confidence: 89%
“…Some NPs are large and spherical while others are small in size with different shapes. 36 Further Fig. 3B shows selected area electron diffraction (SAED) pattern which is in accordance to the crystal plane structure of the nanostructures (Si–TiO 2 NPs) ( Fig.…”
Section: Resultssupporting
confidence: 61%
“…These events were related to different thermal peaks that were observed in the calorimetry curve (DSC Figure 2, blue line). Thus, at a temperature of 90 • C, an endothermic peak occurred, associated with a weight loss of 6.31% up to 200 • C; this physicochemical event is related to the removal of water adsorbed on the surface of the powdered material [49,50]. Between 400 and 750 • C, three exothermic peaks were observed at ~481, 564, and 619 • C, which could be attributed to the oxidation of the organic phase present in the system, initially favoring the formation of oxy-carbonates and finally that of the oxide [49][50][51].…”
Section: Thermogravimetric Analysis (Tga) and Differential Scanning C...mentioning
confidence: 99%